The Correlation Between Personal Hygiene and Food Processing in Diarrhea Occurrences on Post-Earthquake And Liquefaction Toddlers In Refugee Camps Of Biromaru Public Health Center - Herawanto Herawanto; Annisa Fitri Rositadinyati; Muh. Jusman Rau; Marselina Marselina; Litha Purwanti (Ghidza: Jurnal Gizi dan Kesehatan, 2020)
Diarrhea can infect victims of disasters due to the poor sanitation and the unavailability of clean water facilities caused by disaster damage. Biromaru Public Health Center is the health center with the highest diarrhea cases in earthquakes and liquefaction disasters. The purpose of this study was to determine the relationship between personal hygiene and food processing on the incidence of diarrheal diseases in post-disaster toddlers in the evacuation area of ​​Biromaru Public Health Center. This research is analytic observational. Samples in the study were 130 respondents, taken using the proportional stratified random sampling method. Data were analyzed using univariate and bivariate analysis with a chi-square test using ɑ = 5%. Chi-square test results showed hand washing with soap habits (ρ = 0,000), nail hygiene (ρ = 0,000) and food processing (ρ = 0,000). The conclusion of this study there is a relationship between hand washing with soap habits with the incidence of toddler diarrhea in the refugee working area of ​​the Biromaru Public Health Center, there is a relationship between nail hygiene with the incidence of toddler diarrhea in the refugee working area of ​​the Biromaru Public Health Center, and there is a relationship between food processing and the incidence of toddler diarrhea in the refugee working area of ​​the Biromaru Public Health Center. We expected mothers/caregivers of toddlers to take hand washing with soap actions, maintain nail hygiene, and process food properly